MUSIBAH DAN PANDEMI COVID-19: PEMBACAAN MAQĀṢIDĬ TERHADAP AYAT MUSIBAH DALAM AL-QUR’AN - Muhammad Arman Al Jufri (IAIN Madura, 2022)
Assumptions regarding the Covid-19 pandemic as a disaster in a negative interpretation have become a phenomenon in people's lives. Misguided assumptions about the spread of the Covid-19 Pandemic cannot be fully justified. This article examined the meaning of calamities and pandemics, especially the reading of maqāṣidĭ on disaster verses in the Al-Qur'an. This research utilized a qualitative approach with a literature review method. The material objects in this study include verses related to calamities in the Al-Qur'an. While the formal object includes the maqāṣidĭ interpretation approach of Abdul Mustaqim. The three points outlined include disaster theology in the Qur'an through reading maqāṣidĭ interpretations, classification of disasters and the Covid-19 pandemic, and the relationship between the Covid-19 pandemic and disaster in two tendencies of meaning. The results of this study indicated that the calamity referred to in the Qur'an is everything that befalls humans which happens by His will. The classification of disasters in the Covid-19 pandemic is both a blessing and a misfortune. Through ḥifz adjustments, the disaster meaning against the Covid-19 pandemic includes not only negative meanings, but also positive meanings.